Rhegmatogenous retinal detachment with giant retinal tear in a child with Marfan's syndrome: a rare ocular emergency. Issue 6 (2nd June 2021) - Sehgal, Parrina; Narang, Subina; Chandra, Deepak
Abstract : A 7-year-old boy with Marfanoid habitus presented with sudden and painless decrease in the vision of the right eye. Ocular examination revealed rhegmatogenous retinal detachment with 360° giant retinal tear in the right eye and small peripheral retinal breaks with lattice degeneration in the left eye. The patient underwent a 23-gauge pars plana vitrectomy with scleral buckling in the right eye and laser around the breaks in the left eye. At 1-week follow-up visit, the child presented with similar complaints in the left eye as were seen in the right eye. This was later managed effectively with 23-gauge pars plana vitrectomy only. So, with our case report, we would like to highlight the need for aggressive screening in children who are diagnosed with Marfan's syndrome and the need for prophylactic treatment in the unaffected eye.